Learning to BREATHE “Plus”: A Multi-Modal Adaptive Supplement to an Evidence-Based Mindfulness Intervention for Adolescents - Lucas-Thompson, Rachel G.; Rayburn, Stephanie; Seiter, Natasha S.; Broderick, Patricia C.; Smyth, Joshua M.; Coatsworth, J. Douglas; Henry, Kimberly L. (Frontiers in Public Health, 2020)
Incorporating technological supplements into existing group mindfulness-based interventions (MBIs), particularly for use with adolescents, is an important next step in the implementation of MBIs. Yet there is little available content. Herein we present the development and content of a technological supplement for MBIs, which incorporates multiple technological elements to support (a) skill transfer from the group MBI to daily life, (b) the establishment of a formal mindfulness practice, and (c) the use of mindfulness during periods of high stress. A mixed-methods approach was used to develop this multi-method adaptive supplement. Findings about the use of this supplement will be disseminated scientifically and/or publicly as appropriate.